Plant Surfaces: Structures and Functions for Biomimetic Innovations - Barthlott, Wilhelm; Mail, Matthias; Bhushan, Bharat; Koch, Kerstin (Nano-Micro Letters, 2017)
An overview of plant surface structures and their evolution is presented. It combines surface chemistry and architecture with their functions and refers to possible biomimetic applications. Within some 3.5 billion years biological species evolved highly complex multifunctional surfaces for interacting with their environments: some 10 million living prototypes (i.e., estimated number of existing plants and animals) for engineers. The complexity of the hierarchical structures and their functionality in biological organisms surpasses all abiotic natural surfaces: even superhydrophobicity is restricted in nature to living organisms and was probably a key evolutionary step with the invasion of terrestrial habitats some 350–450 million years ago in plants and insects. Special attention should be paid to the fact that global environmental change implies a dramatic loss of species and with it the biological role models. Plants, the dominating group of organisms on our planet, are sessile organisms with large multifunctional surfaces and thus exhibit particular intriguing features. Superhydrophilicity and superhydrophobicity are focal points in this work. We estimate that superhydrophobic plant leaves (e.g., grasses) comprise in total an area of around 250 million km2, which is about 50% of the total surface of our planet. A survey of structures and functions based on own examinations of almost 20,000 species is provided, for further references we refer to Barthlott et al. (Philos. Trans. R. Soc. A 374: 20160191, <a id="ref-link-section-d62720e380" title="W. Barthlott, M. Mail, C. Neinhuis, Superhydrophobic hierarchically structured surfaces in biology: evolution, structural principles and biomimetic applications. Philos. Trans. R. Soc. A 374(2073), 20160191 (2016). doi: 10.1098/rsta.2016.0191 " href="https://link.springer.com/article/10.1007/s40820-016-0125-1#ref-CR1" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 1">1). A basic difference exists between aquatic non-vascular and land-living vascular plants; the latter exhibit a particular intriguing surface chemistry and architecture. The diversity of features is described in detail according to their hierarchical structural order. The first underlying and essential feature is the polymer cuticle superimposed by epicuticular wax and the curvature of single cells up to complex multicellular structures. A descriptive terminology for this diversity is provided. Simplified, the functions of plant surface characteristics may be grouped into six categories: (1) mechanical properties, (2) influence on reflection and absorption of spectral radiation, (3) reduction of water loss or increase of water uptake, moisture harvesting, (4) adhesion and non-adhesion (lotus effect, insect trapping), (5) drag and turbulence increase, or (6) air retention under water for drag reduction or gas exchange (Salvinia effect). This list is far from complete. A short overview of the history of bionics and the impressive spectrum of existing and anticipated biomimetic applications are provided. The major challenge for engineers and materials scientists, the durability of the fragile nanocoatings, is also discussed.